Komentar in kritični prevod slovničnega uvoda v italijansko-slovenskem slovarju Alasia da Sommaripe (1608) - Ahačič, Kozma (Slavistična revija, 2008)
The article presents a commnetary and a critical translation of the grammar introduction in the Italian-Slovene dictionary by Alasia da Sommaripa (1607). It disambiguates more difficult and hard-to-understand passages and places Alasia's grammar in the general European context of its time.
Keywords: 1607; Alasia da Sommaripa, Gregorio, 1578-1626; Alasia da Sommaripa, Gregorio: Vocabolario Italiano e Schiauo; dvojezični slovarji; grammar; Italian; italijanščina; slovarji; Slovene; slovenščina; slovnica; zgodovina jezikoslovja